Combustion characteristics of lignite-water slurries - Yavuz, Reha; Küçükbayrak, Sadriye; Williams, Alan (Elsevier BV, 1998)
Coal water slurries have been developed over the last 15 years as an alternative to fuel oil mainly in industry and power station boilers. They are also a considerable potential for gasification applications, blast furnace injection and fluidized bed combustors. Determination and improvement of combustion characteristics of coal-water slurries are as important as the preparation of the suitable slurry. Suspended single droplet combustion technique may be the best of the methods used in the investigation of combustion characteristics of liquid fuel droplets. The main advantage of this technique is that, droplet lifetime history, ignition delay, flame structure, centre and surface temperature of the droplet and burning rate can be investigated and a good comparative result for different fuels under the same conditions can be obtained. Therefore, suspended single droplet combustion technique was used in this study. The effect of droplet size, lignite fraction in the slurry and furnace temperature on slurry combustion were studied systematically.